Left atrial appendage volume is an independent predictor of atrial arrhythmia recurrence following cryoballoon pulmonary vein isolation in persistent atrial fibrillation - Pongratz, J.; Riess, L.; Hartl, S.; Brueck, B.; Tesche, C.; Ebersberger, U.; Helmberger, T.; Crispin, A.; Wankerl, M.; Dorwarth, U.; Hoffmann, E.; Straube, F. (Frontiers in Cardiovascular Medicine, 2023)
PURPOSE Pulmonary vein isolation (PVI) is the cornerstone of atrial fibrillation (AF) ablation in persistent AF (persAF), and cryoballoon PVI emerged as an initial ablation strategy. Symptomatic AF recurrence following successful PVI in persAF is observed in a relevant number of patients. Predictors for arrhythmia recurrence following cryoballoon PVI for persAF are not well described, and the role of left atrial appendage (LAA) anatomy is uncertain. METHODS Patients with symptomatic persAF and pre-procedural cardiac computed tomography angiography (CCTA) images undergoing initial second-generation cryoballoon (CBG2) were enrolled. Left atrial (LA), pulmonary vein (PV) and LAA anatomical data were assessed. Clinical outcome and predictors for AF recurrence were evaluated by univariate and multivariate regression analysis. RESULTS From May 2012 to September 2016, 488 persAF patients underwent CBG2-PVI. CCTA with sufficient quality for measurements was available in 196 (60.4%) patients. Mean age was 65.7±9.5 years. Freedom from arrhythmia was 58.2% after a median follow-up of 19 (13; 29) months. No major complications occurred. Independent predictors for arrhythmia recurrence were LAA volume (HR 1.082; 95% CI, 1.032 to 1.134; p=0.001) and mitral regurgitation ≥ grade 2 (HR, 2.49; 95% CI 1.207 to 5.126; p=0.013). LA volumes ≥110.35ml (sensitivity: 0.81, specificity: 0.40, area under the curve (AUC)=0.62) and LAA volumes ≥9.75ml (sensitivity: 0.56, specificity 0.70, AUC=0.64) were associated with recurrence. LAA-morphology, classified as chicken-wing (21.9%), windsock (52.6%), cactus (10.2%) and cauliflower (15.3%), did not predict outcome (log-rank, p=0.832). CONCLUSION LAA volume and mitral regurgitation were independent predictors for arrhythmia recurrence following cryoballoon ablation in persAF. LA volume was less predictive and correlated with LAA volume. LAA morphology did not predict the clinical outcome. To improve outcomes in persAF ablation, further studies should focus on treatment strategies for persAF patients with large LAA and mitral regurgitation.